IMPROVING NOBLE GAS BASED PALEOCLIMATE RECONSTRUCTION AND GROUNDWATER DATING USING 20NE/22NE RATIOS - Peeter F.; Aeschbach-Hertig W.; Holocher J.; Brennwald M.S.; Kipfer R.; Beyerle U. (My University, 2003)
The interpretation of noble gas concentrations in groundwater with respect to recharge temperature and fractionated excess gas leads to different results on paleo-climatic conditions and on residence times depending on the choice of the gas partitioning model. Two fractionation models for the gas excess are in use, one assuming partial re-equilibration of groundwater supersaturated by excess air (PR-model, Stute et al., 1995), the other assuming closed-system equilibration of groundwater with entrapped air (CE-model, Aeschbach-Hertig et al., 2000). In the example of the Continental Terminal aquifers in Niger, PR- and CE-model are both consistent with the data on elemental noble gas concentrations (Ne, Ar, Kr, and Xe). Only by including the isotope ratio 20Ne/22Ne it can be demonstrated that the PR-model has to be rejected and the CE-model should be applied to the data. In dating applications 3He of atmospheric origin (3Heatm) required to calculate 3H-3He water ages is commonly estimated from the Ne excess presuming that gas excess is unfractionated air (UA-model). Including in addition to the Ne concentration the 20Ne/22Ne ratio and the concentration of Ar enables a rigorous distinction between PR-, CE- and UA-model and a reliable determination of 3Heatm and of 3H-3He water ages.